Faculty profile: Professor Liew Kong Yong, physical chemist - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)

(untitled)
Liew Kong Yong was born and raised in a small town in Perak in 1946. He received his early education in a Chinese medium school, went on to the big city of lpoh to finish high school and then to Universiti Malaya to obtain his B.Sc. in mathematics and chemistry.